Multiple Epidermoid Cyst on Frenulum and Ventral Preputium of the Penis: A Case Report - Dimas Bintoro Kresna Yustisia Handoyo; I Wayan Jorden Junior; Gede Wirya Kusuma Duarsa; Aris Rosidah (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2023)
Penile epidermoid cyst are uncommon cases and more rare with a multiple cyst on the penile. We presented a twelve-year-old male patient with a case of 1 month growing, mobilized, non-tender frenulum and ventral preputium of the penis mass. Circumcision and total excision was performed under local anesthesia. Pathological examination was revealed as epidermoid cyst. Observation was carried out on the patient, first control the patient has a recurrent nodule grew only on the frenulum and aspiration was carried out and administration of antibiotics and corticosteroid was given, second control patient came to complete recovery.